What contributes to drug driving? An exploratory investigation into the influence of problematic substance use, roadside testing and alternative transport options. (May 2023) - Hasan, Razi; Watson, Barry; Haworth, Narelle; Oviedo-Trespalacios, Oscar
Highlights: Cannabis is the most reported drug used by drug drivers in Australia. Self-reported problematic drug use is associated with drug driving. Knowledge of penalties is associated with engaging in drug driving. No association was found between observing RDT and drug driving. Drug drivers report using a variety of strategies to evade detection. Abstract: Despite a strong reliance on enforcement approaches to prevent drug driving in Australia, this behaviour is still prevalent. The objective of this study was to investigate the influence of problematic drug use (i.e., showing indications of addiction), exposure to roadside drug testing, the use of detection avoidance strategies, and perceptions relating to alternative transport options on drug driving among illicit drug users. A total of 1, 541 licensed drivers from the states of Queensland, New South Wales, and Victoria completed an online survey. The survey collected demographic and problematic substance use information, as well as items assessing drug driving behaviour. Cannabis was reported to be the most commonly used drug (36.0%); the most common drug of problematic use (27.9%), and the drug most often taken prior to driving (43.5%). Observing police operating Roadside Drug Tests (RDT) was more common among the participants than being tested by RDT (35.7% vs 23%). The results indicated a significant association between being a drug driver and observing or being tested by RDT. The drug drivers were significantly more likely to report using a range of strategies to avoid police detection than the non-drug drivers. Similarly, the drug drivers reported that it was more difficult for them to use various alternative transport options than the non-drug drivers. Decision tree analyses found that significant predictors of self-reported drug driving were problematic drug use, holding a provisional or probationary licence, earning a low- or middle-income, and using detection avoidance strategies like remaining watchful for police vehicles and taking back streets. The findings of this study suggest that ongoing improvements to drug driving enforcement will need to be complemented by health-based approaches designed to reduce drug abuse and dependence, and improvements to public transport, in order to achieve a sustainable reduction in drug driving.